Fishy Odor and TMA Content Levels in Duck Egg Yolks. Issue 1 (6th December 2017) - Li, Xingzheng; Yuan, Gongjiao; Chen, Xia; Guo, Yuying; Yang, Ning; Pi, Jinsong; Zhang, Hao; Zheng, Jiangxia
Abstract : Abstract: The differences between the trimethylamine (TMA) content levels in duck and chicken egg yolks under normal dietary conditions were compared. Moreover, the association between the polymorphisms of the duck FMO3 gene and TMA content levels in duck egg yolks was analyzed. Then, to detect the mutations associated with the fish‐flavor trait, duck populations were selected for a high‐choline diet experiment, which was followed by full‐length sequencing of the FMO3 exons. The results showed that the TMA content levels in duck eggs (3.60 μg/g) were significantly higher than those in chicken eggs (2.35 μg/g) under normal dietary conditions ( P < 0.01). With regard to the high‐choline diet, the average TMA content levels in duck egg yolks (9.21 μg/g; P < 0.01) increased significantly. Furthermore, 5 SNPs reported in Ensembl database were detected in duck FMO3 exons. However, no mutation loci were found to be significantly associated with the TMA content levels in duck egg yolks. Besides, duck liver FMO3 mRNA expression levels were not associated with the TMA content levels. The results indicated that excessive TMA deposition in duck eggs is one of main factors causing the fishy odor in duck eggs, and the addition of choline in the ducks' diets was responsible for inducing an increase in the TMA content levels in duck eggs. Practical Application: Our study can help to diminish the fishy taste in duck eggs by reducing the amount of supplemented choline. Furthermore, this study laid a solid foundation for revealing the genetic factors involved in the fishy odor in duck eggs.